Research Proposal Development in ELT: Tools for Planning, Structuring and Writings - Pandey, Gopal Prasad (NPRC Journal of Multidisciplinary Research, 2024)
The primary objective of this study is to explore the tools and processes involved in developing a research proposal for English Language Teaching (ELT), focusing on effective planning, structuring, and writing practices. A theoretical framework underpinned by constructivist learning theory and sociocultural theory guides the design of the study. The research employs a qualitative approach, synthesizing existing literature and expert guidelines to develop a comprehensive framework for research proposal development. Key stages such as selecting a topic, conducting a literature review, formulating research questions, and outlining methodological strategies are critically analyzed. The study suggests that clear research objectives, grounded in theoretical principles, significantly enhance the coherence and impact of research proposals. Furthermore, the alignment of personal interests with current trends in ELT increases the likelihood of sustained researcher engagement. In addition, the paper presents that a systematic approach to proposal development, incorporating clear objectives and methodological rigor, improves the overall quality and relevance of ELT research. The paper suggest that the incorporation of mentorship and peer feedback in the proposal development process and the necessity for researchers to remain flexible in their methodological choices, adapting them to the research context. This study contributes to the field by providing a structured guideline that can be utilized by novice researchers in ELT.